2002
DOI: 10.2175/106143002x139857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Solids Concentration and Organic Loading on the Performance of Temperature Phased Anaerobic Digestion Process

Abstract: The effect of varying total solids (TS) and volatile solids (VS) concentrations and organic loading on the performance of a temperature phased anaerobic digestion (TPAD) system treating a mixture of primary and waste activated sludges was evaluated. An optimum volatile solids destruction of 61.5% occurred at a feed concentration of 4.9% (corresponding to 3.8% VS concentration) in the system operated at a total detention time of 20 days. At a total solids concentration of 7.9% (5.8% VS concentration), the volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…So far several studies on TPAD process have been reported (Schmit & Ellis 2001;Vandenburgh & Ellis 2002;Sung & Santha 2003), but no study was reported for treating WAS.…”
Section: Introductionmentioning
confidence: 99%
“…So far several studies on TPAD process have been reported (Schmit & Ellis 2001;Vandenburgh & Ellis 2002;Sung & Santha 2003), but no study was reported for treating WAS.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, thermophilic AD (55°C) has been found to improve both biosolids and pathogen destruction over mesophilic AD (35-37°C) [3,36]. Thermophilic digesters have also been shown to better maintain high COD removal eYciencies after increases in organic loading than mesophilic digesters [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…♦ The disadvantages are (Han and Dague, 1997;Vandenburgh and Ellis, 2002) ♦ Higher energy required for thermophilic phase;…”
Section: Digester Gasmentioning
confidence: 99%